2007
DOI: 10.1682/jrrd.2006.06.0063
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of selected complementary and alternative medicine interventions for chronic pain

Abstract: Abstract-Complementary and alternative medicine (CAM)is a group of diverse medical and healthcare systems, therapies, and products that are not presently considered part of conventional medicine. This article provides an up-to-date review of the efficacy of selected CAM modalities in the management of chronic pain. Findings are presented according to the classification system developed by the National Institutes of Health National Center for Complementary and Alternative Medicine (formerly Office of Alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 151 publications
0
24
0
Order By: Relevance
“…However, since CAM treatments typically do not use expensive medical equipment or invasive procedures, the cost is typically lower for CAM treatments than for traditional treatments [50]; Lafferty et al found that median cost of visits to CAM providers was $39.00 versus the median cost of $74.40 for visits to allopathic providers [51]. Importantly, since each of the CAM options studied here has demonstrated effectiveness for chronic pain [27][28][29][30], patient outcomes might be expected to improve as a result of their use. Indeed, one systematic review found evidence to support the cost-effectiveness of CAM modalities, especially for use with migraine and neck pain [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since CAM treatments typically do not use expensive medical equipment or invasive procedures, the cost is typically lower for CAM treatments than for traditional treatments [50]; Lafferty et al found that median cost of visits to CAM providers was $39.00 versus the median cost of $74.40 for visits to allopathic providers [51]. Importantly, since each of the CAM options studied here has demonstrated effectiveness for chronic pain [27][28][29][30], patient outcomes might be expected to improve as a result of their use. Indeed, one systematic review found evidence to support the cost-effectiveness of CAM modalities, especially for use with migraine and neck pain [52].…”
Section: Discussionmentioning
confidence: 99%
“…We chose these modalities because they have been supported by prior research for use with chronic pain [27][28][29][30] but may not necessarily be offered as a treatment option in VA facilities. The CAM items were embedded in a 15-item measure that assessed various approaches to pain management.…”
Section: Cam Treatment Use and Willingnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The Veteran’s goal is to find new approaches to managing and/or rehabilitating from chronic pain, anxiety, post-traumatic stress disorder (PTSD), and other troubling symptoms, which significantly affect health and quality of life. Research on many of these therapies has shown promising results [2–8]. The Department of Veterans Affairs (VA) is exploring ways to meet this demand for access to CIH when combined with conventional medical care.…”
Section: Introductionmentioning
confidence: 99%
“…In line with these recommendations, sustained expansion of specialty pain medicine services over the past 5 years has been documented. Consistent with data on patient preferences [36], VHA is working to build capacity for complementary and alternative medicine services [37], especially acupuncture [38,39]. Models of integrative care are emerging [31,40] and are beginning to be evaluated for their efficacy and, ultimately, their cost-effectiveness.…”
Section: Step 2: Specialty Carementioning
confidence: 99%